Hindu Gods in West Africa Ghanaian Devotees of Shiva and Krishna. - Wuaku, Albert Kafui, 1964- (Leiden : BRILL, 2013)
In Hindu Gods in West Africa, Wuaku offers an analytical account of the histories, beliefs and practices of the Hindu Monastery of Africa and the Radha Govinda Temple, two of Ghana's emmerging Hindu Temples.
Acknowledgements; Introduction; Chapter One Ghana's Hindu Religious Landscape; Chapter Two The Hindu Monastery of Africa; Chapter Three Domesticating Shiva Worship in Ghana: Rituals of the Hindu Monastery of Africa; Chapter Four The Sri Radha-Govinda Temple Tradition; Chapter Five "Hinduizing" From the "Top," Indigenizing from "Below": Krishna Devotion in Ghana; Chapter Six Spreading Krishna and Shiva Worship in Ghana; Chapter Seven Why We became Hindus: Conversion Narratives; Chapter Eight Conclusion; Bibliography; Index; Illustration Section.
Description based on print version record.
Keywords: Ghana -- Religious life and customs; Hinduism -- Ghana -- History; Hinduism -- Ghana -- Customs and practices; Hindus -- Ghana; RELIGION / Comparative Religion; Hindus -- Ghana; Hinduism -- Ghana -- History; Hinduism -- Ghana -- Customs and practices; Ghana -- Religious life and customs; Electronic books